2011
DOI: 10.1128/jcm.02447-10
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Hepatitis C Virus, HIV, and Hepatitis B Virus Nucleic Acids in Plasma Samples after Long-Term Storage at −20 o C and −70 o C

Abstract: The storage of biological samples may affect detection of viral nucleic acid, yet the stability of viral nucleic acid at standard laboratory storage temperatures (؊70°C and ؊20°C) has not been comprehensively assessed. Deterioration of viral RNA and DNA during storage may affect the detection of viruses, thus leading to an increased likelihood of false-negative results on diagnostic testing. The viral loads of 99 hepatitis C virus (HCV), 41 HIV, and 101 hepatitis B virus (HBV) patient samples were measured bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
25
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 20 publications
1
25
2
Order By: Relevance
“…Most studies have demonstrated that when plasma is frozen in separate aliquots there is minimal degradation of viral DNA or RNA over time . This, however, was not the case for HCV RNA in this study, where we observed a 50% decrease in viral load, or for HBV DNA, where the viral load increased.…”
Section: Discussioncontrasting
confidence: 82%
See 4 more Smart Citations
“…Most studies have demonstrated that when plasma is frozen in separate aliquots there is minimal degradation of viral DNA or RNA over time . This, however, was not the case for HCV RNA in this study, where we observed a 50% decrease in viral load, or for HBV DNA, where the viral load increased.…”
Section: Discussioncontrasting
confidence: 82%
“…However, there are few published studies describing the effect of freezing and thawing samples in PPTs, especially in terms of viral stability or qualitative detection of viral nucleic acids and antibodies and/or antigens. Where studies are available, either they are limited to a short storage period, restricted to one or two viral analytes, or they examine only plasma or serum aliquots . We therefore conducted this study to demonstrate that frozen and thawed plasma stored for long periods in a PPT continue to provide reliable qualitative blood donor NAT and serology screening results for HIV, HCV, and HBV for up to 36 months after freezing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations